CBCT Diagnostic Application In Detection Of Mesiobuccal Canal In Maxillary Molars And Distolingual Canal In Mandibular Molars: A Descriptive Study - Aws Hashim Al-Kadhim; Ainul Husna Abd Latib; Nur Fazireen Nordin (Scient Open Access, 2024)
Volume 1 • Issue 1 . 2015